Application of standardized platelet‐rich plasma in elderly patients with complex wounds. Issue 3 (12th February 2019) - Tian, Ju; Cheng, Liu‐Hang‐Hang; Cui, Xiao; Lei, Xiao‐Xuan; Tang, Jian‐Bing; Cheng, Biao
Abstract: In recent years, autologous platelet‐rich plasma (PRP) derivatives have been used widely in the regeneration and repair of tissue, but a standard definition and preparation method for PRP are lacking. We developed a standardized method using platelet indices as quality‐control indicators for PRP preparation. Twenty‐one elderly patients (9 males, 12 females) with complex wounds were treated with standardized platelet‐rich plasma (S‐PRP). The platelet count in PRP after the second centrifugation was 1, 069–1, 436 × 10 9 /L. We adjusted the platelet concentration in PRP after a second centrifugation to 1, 000 × 10 9 /L according to a formula using platelet‐poor plasma (PPP). The standardized preparation method that we developed gave S‐PRP with a relatively uniform platelet concentration. The wounds of 21 patients showed accelerated healing after S‐PRP treatment, and there were no obvious side effects during treatment. These data suggest that our preparation method of S‐PRP, using platelet indices as quality‐control indicators with platelet count of 1, 000 × 10 9 /L could be used for the treatment of complex wounds in the elderly. The preparation method of S‐PRP proposed in the present study may be a simple and effective method of PRP quality control.